Digital linkage and innovation promotion: An empirical study on the development of green economy in China and Belarus under the background of the belt and road initiative - Song, Xin; Han, Wenyuan; Wang, Zining; Cheng, Xinwen; Zongyu, Luo (Edelweiss Applied Science and Technology, 2025)
This study focuses on the economic cooperation between China and Belarus in the digital field against the backdrop of the Belt and Road Initiative. Through the panel regression model, multi-dimensional data such as the economic value of scientific and technological innovation output and the level of digitalization in the five Central Asian countries and countries along the Belt and Road are analyzed. The results show that after considering geographical and economic factors, the positive impact of scientific and technological innovation value on promoting innovation has weakened, highlighting the importance of regional cooperation in the Belt and Road Economic Circle. Further analysis confirmed that China is an ideal partner for Belarus in the economic field. The study recommends strengthening cooperation between the two countries in scientific and technological innovation, digital economic levels, and overall economic construction to promote the harmonious and innovative development of green economic digitalization.